2017
DOI: 10.3389/fchem.2017.00010
|View full text |Cite
|
Sign up to set email alerts
|

Tb3+-Cleavage Assays Reveal Specific Mg2+ Binding Sites Necessary to Pre-fold the btuB Riboswitch for AdoCbl Binding

Abstract: Riboswitches are RNA elements that bind specific metabolites in order to regulate the gene expression involved in controlling the cellular concentration of the respective molecule or ion. Ligand recognition is mostly facilitated by Mg2+ mediated pre-organization of the riboswitch to an active tertiary fold. To predict these specific Mg2+ induced tertiary interactions of the btuB riboswitch from E. coli, we here report Mg2+ binding pockets in its aptameric part in both, the ligand-free and the ligand-bound form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…6 b) [ 142 ]. It has recently been shown that Mg(II) can pre-organise the btuB riboswitch into a binding-competent conformation that recognises AdoCbl [ 143 ]. Binding affinities for B 12 riboswitches range from 2.5 × 10 −7 M for AdoCbl ( btuB riboswitch) to 7.5 × 10 −9 M for MeCbl ( env8AqCbl riboswitch) [ 142 ].…”
Section: The Components Of Cobalt Homeostasismentioning
confidence: 99%
“…6 b) [ 142 ]. It has recently been shown that Mg(II) can pre-organise the btuB riboswitch into a binding-competent conformation that recognises AdoCbl [ 143 ]. Binding affinities for B 12 riboswitches range from 2.5 × 10 −7 M for AdoCbl ( btuB riboswitch) to 7.5 × 10 −9 M for MeCbl ( env8AqCbl riboswitch) [ 142 ].…”
Section: The Components Of Cobalt Homeostasismentioning
confidence: 99%